The effect of stimulus intensity on response time and accuracy in dynamic, temporally constrained environments - Causer, J.; McRobert, A. P.; Williams, A. M. (Scandinavian Journal of Medicine & Science in Sports, 2013)
The ability to make accurate judgments and execute effective skilled movements under severe temporal constraints are fundamental to elite performance in a number of domains including sport, military combat, law enforcement, and medicine. In two experiments, we examine the effect of stimulus strength on response time and accuracy in a temporally constrained, real-world, decision-making task. Specifically, we examine the effect of low stimulus intensity (black) and high stimulus intensity (sequin) uniform designs, worn by teammates, to determine the effect of stimulus strength on the ability of soccer players to make rapid and accurate responses. In both field- and laboratory-based scenarios, professional soccer players viewed developing patterns of play and were required to make a penetrative pass to an attacking player. Significant differences in response accuracy between uniform designs were reported in laboratory- and field-based experiments. Response accuracy was significantly higher in the sequin compared with the black uniform condition. Response times only differed between uniform designs in the laboratory-based experiment. These findings extend the literature into a real-world environment and have significant implications for the design of clothing wear in a number of domains.